Southwestern Thrace: ethnocultural problems (11th–6th centuries BCE) - Georgieva, Rumjana (Balcanica Posnaniensia. Acta et studia, 1990)
The article addresses the problem of reconstructing the ethnocultural development of southwestern Thrace from the 11th to the mid-6th century BC, which remains poorly recognized and is often incorrectly framed within the broadly understood “Macedonia.” The problem is significant because previous interpretations lead to inaccuracies in identifying the ethnic and cultural affiliation of the region and obscure its specificity. The aim of the work is a critical verification of these approaches and an attempt to reconstruct the actual picture of cultural transformations in the studied area. The author applies a comprehensive research method, combining the analysis of archaeological materials, linguistic data (anthroponyms and toponyms), and written sources. The most important results indicate that in the Late Bronze Age and Early Iron Age at least two main cultural zones developed, associated with Chalkidiki and the lower course of the Vardar, and with the areas of the Devol and Haliakmon rivers. In the 11th–10th centuries BC, cultural unity of the region is visible, accompanied by the influx of elements from the Middle Danube area, which indicates population migrations and wide interregional contacts. In the 8th century BC, clear cultural differentiation occurred, connected with the influx of Illyrian influences and the development of local variants of culture, especially east of the Vardar. It was also established that several cultural zones existed, which remained in dynamic relations with each other but did not form a uniform complex. The conclusion of the work is that southwestern Thrace developed as an area with a complex, multilayered ethnocultural structure that cannot be reduced to a single “Macedonian” model, and its history was the result of both local continuity and external influences.